The interaction of resource use and gene flow on the phenotypic divergence of benthic and pelagic morphs of Icelandic Arctic charr (Salvelinus alpinus). Issue 12 (2nd May 2021) - Brachmann, Matthew K.; Parsons, Kevin; Skúlason, Skúli; Ferguson, Moira M.
Abstract: Conceptual models of adaptive divergence and ecological speciation in sympatry predict differential resource use, phenotype–environment correlations, and reduced gene flow among diverging phenotypes. While these predictions have been assessed in past studies, connections among them have rarely been assessed collectively. We examined relationships among phenotypic, ecological, and genetic variation in Arctic charr ( Salvelinus alpinus ) from six Icelandic localities that have undergone varying degrees of divergence into sympatric benthic and pelagic morphs. We characterized morphological variation with geometric morphometrics, tested for differential resource use between morphs using stable isotopes, and inferred the amount of gene flow from single nucleotide polymorphisms. Analysis of stable isotopic signatures indicated that sympatric morphs showed similar difference in resource use across populations, likely arising from the common utilization of niche space within each population. Carbon isotopic signature was also a significant predictor of individual variation in body shape and size, suggesting that variation in benthic and pelagic resource use is associated with phenotypic variation. The estimated percentage of hybrids between sympatric morphs varied across populations (from 0% to 15.6%) but the majority of fish had genotypes (ancestry coefficients) characteristic of pure morphs. Despite evidence of reduced gene flow between sympatric morphs, we did not detect the expected negative relationship between divergence in resource use and gene flow. Three lakes showed the expected pattern, but morphs in the fourth showed no detectable hybridization and had relatively low differences in resource use between them. This coupled with the finding that resource use and genetic differentiation had differential effects on body shape variation across populations suggests that reproductive isolation maintains phenotypic divergence between benthic and pelagic morphs when the effects of resource use are relatively low. Our ability to assess relationships between phenotype, ecology, and genetics deepens our understanding of the processes underlying adaptive divergence in sympatry. Abstract : Our study assesses the contribution of differential resource use, phenotype–environment correlations, and reductions in gene flow to adaptive divergence of benthic–pelagic morphs of Icelandic Arctic charr in sympatry. We integrate a variety of analytical approaches to test our hypotheses using geometric morphometrics, stable isotopic signatures, and single nucleotide polymorphisms. Resource use appears to be the agent of selection driving phenotypic divergence along a benthic–pelagic axis and reproductive isolation may maintain this divergence when the intensity of divergent selection is weak. ​